2020
DOI: 10.3389/fpls.2020.00205
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of Sex Chromosomes in Silene latifolia and S. dioica Was Accompanied by Multiple Chromosomal Rearrangements

Abstract: The genus Silene includes a plethora of dioecious and gynodioecious species. Two species, Silene latifolia (white campion) and Silene dioica (red campion), are dioecious plants, having heteromorphic sex chromosomes with an XX/XY sex determination system. The X and Y chromosomes differ mainly in size, DNA content and posttranslational histone modifications. Although it is generally assumed that the sex chromosomes evolved from a single pair of autosomes, it is difficult to distinguish the ancestral pair of chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 57 publications
1
23
0
Order By: Relevance
“…Silene sect. Melandrium, Phoenix ) (Cherif et al ., 2016; Bačovský et al ., 2020), homologous sex chromosomes between different genera have never been described in plants so far. This situation is in stark contrast to the situation in animals, for which several systems are > 100 Myr old and are shared by whole classes, for example, birds and mammals (Ohno, 1969; Fridolfsson et al ., 1998; Cortez et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Silene sect. Melandrium, Phoenix ) (Cherif et al ., 2016; Bačovský et al ., 2020), homologous sex chromosomes between different genera have never been described in plants so far. This situation is in stark contrast to the situation in animals, for which several systems are > 100 Myr old and are shared by whole classes, for example, birds and mammals (Ohno, 1969; Fridolfsson et al ., 1998; Cortez et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These oligos can then be synthesized in parallel and labeled as a FISH probe (Han et al ., 2015). Chromosomal research based on such pooled oligo probes has been reported in a rapidly increasing number of plant species (Qu et al ., 2017; Braz et al ., 2018; He et al ., 2018; Hou et al ., 2018; Meng et al ., 2018; Xin et al ., 2018; Albert et al ., 2019; Martins et al ., 2019; Simonikova et al ., 2019; Bačovský et al ., 2020; Bi et al ., 2020; Braz et al ., 2020a; Liu et al ., 2020; Song et al ., 2020; Xin et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Oligo‐FISH is an excellent tool to investigate chromosome evolution among genetically related species (Bačovský et al., 2020 ; Bi et al., 2020 ; Braz et al., 2018 ; Xin et al., 2020 ). The applicability of an oligo‐FISH probe in a different species will depend on the level of sequence conservation of the selected oligos among the two species (Braz et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%